Recovery of the gut microbiome following enteric infection and persistence of antimicrobial resistance genes in specific microbial hosts - Zoe A. Hansen; Karla Vasco; James T. Rudrik; Kim T. Scribner; Lixin Zhang; Shannon D. Manning (Scientific Reports, 2023)
Abstract Enteric pathogens cause widespread foodborne illness and are increasingly resistant to important antibiotics yet their ecological impact on the gut microbiome and resistome is not fully understood. Herein, shotgun metagenome sequencing was applied to stool DNA from 60 patients (cases) during an enteric bacterial infection and after recovery (follow-ups). Overall, the case samples harbored more antimicrobial resistance genes (ARGs) with greater resistome diversity than the follow-up samples (p < 0.001), while follow-ups had more diverse gut microbiota (p < 0.001). Although cases were primarily defined by genera Escherichia, Salmonella, and Shigella along with ARGs for multi-compound and multidrug resistance, follow-ups had a greater abundance of Bacteroidetes and Firmicutes phyla and resistance genes for tetracyclines, macrolides, lincosamides, and streptogramins, and aminoglycosides. A host-tracking analysis revealed that Escherichia was the primary bacterial host of ARGs in both cases and follow-ups, with a greater abundance occurring during infection. Eleven distinct extended spectrum beta-lactamase (ESBL) genes were identified during infection, with some detectable upon recovery, highlighting the potential for gene transfer within the community. Because of the increasing incidence of disease caused by foodborne pathogens and their role in harboring and transferring resistance determinants, this study enhances our understanding of how enteric infections impact human gut ecology.